DOLOM ITELIME ADMINISTRATION WITH DIFFERENT DOSES ON THE MAINTENANCE OF BAUNG FISH (Hemibagrusnemurus) WITH BIOFLOK TECHNOLOGY - Rahmi Rahmi; Rusliadi Rusliadi; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACKThis research has been implemented in June-July 2019 at the Faculty of Fisheries and Marine of Riau University. The purpose of this research is to know the best dose of dolomite lime in the growth of Baung fish (Hemibagrusnemurus) using the Bioflok system. The method used in this research is the experimental method by using RAL (complete random draft), with 4 treatment levels and 3 repeats, with the following treatment: (1) P1:100 gr/m3 or 4 gr/40 L, (2) P2: the addition of Dolomite limestone 150 gr/m3 or 6 gr/40 L, (3) P3: The provision of limestone dolomite as much as 200 gr/m3 or 8 gr/40 L and (4) P4: the addition of Dolomite limestone 240 gr/m3 or 10 gr/40 L. The best result of this study is on P3 treatment = The addition of dolomite limestone 200 gr/m3 (8GR/40 L) with the quality of water during the research temperature 28 0C, Ammoniac 0,0003-0,0006 mg/L, DO4,37-4.77 mg/L, pH 6-7. Then on growth and livelihood is on the growth of the average Ratar 4.4 gr, the total weight growth is 2.39 g, average growth of average 8.66 cm, the total growth of absolute 2.74 cm, growth rate Pesifik 2.579%, life cycle 97% and Volume FLOC 5.8 ml/L.Kata Kunci :Molase, BioflokHemibagrusnemurus, KapurDolomit,